Genome-wide Association of Kidney Traits in Hispanics/Latinos Using Dense Imputed Whole Genome Sequencing Data: The Hispanic Community Health Study/Study of Latinos - Qian, Huijun (Circ Genom Precis Med, 2020)
BACKGROUND -: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS -: This study used imputed whole genome sequencing from the Trans-Omics for Precision Medicine project to identify novel loci for estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (ACR) in up to 12,207 Hispanics/Latinos. Replication was performed in the Women’s Health Initiative and the UK Biobank when variants were available. RESULTS -: Two low frequency intronic variants were associated with eGFR (rs58720902 at AQR, minor allele frequency [MAF] = 0.01, P=1.6 × 10(−8)) or ACR (rs527493184 at ZBTB16, MAF=0.002, P=1.1 × 10(−8)). An additional variant at PRNT (rs2422935, MAF=0.54, P=2.89 × 10(−8)) was significantly associated with eGFR in meta-analysis with replication samples. We also identified two known loci for ACR (BCL2L11 rs116907128, P=5.6 × 10(−8) and HBB rs344, P=9.3 × 10(−11)) and validated eight loci for ACR previously identified in the UK Biobank. CONCLUSIONS -: Our study shows gains in gene discovery when using dense imputation from multi-ethnic whole genome sequencing data in admixed Hispanics/Latinos. It also highlights limitations in genetic research of kidney traits, including the lack of suitable replication samples for variants that are more common in non-European ancestry and those at low frequency in populations.